2016
DOI: 10.1255/jnirs.1232
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Physical Protection of Soil Carbon with Quantitative Infrared Spectroscopy

Abstract: Near infrared (NIR) and mid-infrared (mid-IR) reflectance spectroscopy are time-and cost-effective tools for characterising soil organic carbon (SOC). Here they were used for quantifying (i) carbon (C) dioxide (CO 2 ) emission from soil samples crushed to 2 mm and 0.2 mm, at 18°C and 28°C; (ii) physical C protection, calculated as the difference between CO 2 emissions from 0.2 mm and 2 mm crushed soil at a given temperature; and (iii) the temperature vulnerability of this protection, calculated as the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
(94 reference statements)
1
17
0
Order By: Relevance
“…Many papers have reported better prediction of SOC concentration using MIR than (V)NIR spectra (Dong et al, 2011;Igne et al, 2010;McCarty et al, 2002;Reeves et al, 2002;Reeves, McCarty, & Reeves, 2001;Viscarra Rossel, Walvoort, McBratney, Janik, & Skjemstad, 2006;Xie, Yang, Drury, Yang, & Zhang, 2011); but it is worth noting that they concerned temperate regions (except Dong et al, 2011), and rather homogeneous soil sample sets in general. The trend was less clear in other studies (Madari et al, 2005;Yang et al, 2012), while some even reported better NIRS than MIRS predictions (Madari et al, 2006;Ludwig, Nitschke, Terhoeven-Urselmans, Michel, & Flessa, 2008;Rabenarivo et al, 2013;Barthès et al, 2016;and also Shao & He, 2011, for N concentration), regarding tropical and subtropical regions (except Ludwig et al, 2008) and more diverse sample sets.…”
Section: Spectral Range: (V)nirs Versus Mirsmentioning
confidence: 77%
See 3 more Smart Citations
“…Many papers have reported better prediction of SOC concentration using MIR than (V)NIR spectra (Dong et al, 2011;Igne et al, 2010;McCarty et al, 2002;Reeves et al, 2002;Reeves, McCarty, & Reeves, 2001;Viscarra Rossel, Walvoort, McBratney, Janik, & Skjemstad, 2006;Xie, Yang, Drury, Yang, & Zhang, 2011); but it is worth noting that they concerned temperate regions (except Dong et al, 2011), and rather homogeneous soil sample sets in general. The trend was less clear in other studies (Madari et al, 2005;Yang et al, 2012), while some even reported better NIRS than MIRS predictions (Madari et al, 2006;Ludwig, Nitschke, Terhoeven-Urselmans, Michel, & Flessa, 2008;Rabenarivo et al, 2013;Barthès et al, 2016;and also Shao & He, 2011, for N concentration), regarding tropical and subtropical regions (except Ludwig et al, 2008) and more diverse sample sets.…”
Section: Spectral Range: (V)nirs Versus Mirsmentioning
confidence: 77%
“…The supposedly superior performance of MIRS has been attributed to the richer information it provides (cf. Importantly, Barthès et al (2016) reported noticeably poorer MIRS predictions using spectra acquired on 2-than on 0.2-mm samples; thus MIRS requires fine grinding, which is somewhat tedious and contradicts the time-and cost-effectiveness of the approach. In contrast, these authors found little difference in SOC prediction accuracy when NIR spectra were acquired on 2-vs. 0.2-mm samples.…”
Section: Spectral Range: (V)nirs Versus Mirsmentioning
confidence: 99%
See 2 more Smart Citations
“…While applications of NIR spectroscopy for assessments of soil organic matter date back to earlier work in the 1980s 1 the papers in this issue bring new insights to its potential benefits. For example, Barthès et al 2 report a detailed comparison of the benefits of NIR and mid-infrared spectra to analyse soil organic and inorganic carbon and suggest how temperature and sample preparation influence the protected carbon in a soil sample.…”
mentioning
confidence: 99%